The Role Of The Borsom System In Shaping The Relationship Between Income And Welfare Of Rural Palm Sugar Artisans: An Islamic Economics Perspective - Novia Purnamasari; Umi Narimawati; Bobi Kurniawan; Agus Riyanto; Raeni Dwisanty (Jesya, 2026)
This study examines the mechanisms through which the borsom system shapes the relationship between income and economic welfare among rural palm sugar artisans from an Islamic economic perspective. Using a qualitative approach, data were collected through in-depth interviews, field observations, and documentation involving palm sugar artisans in Banyuwangi Village, Sukabumi Regency. The findings indicate that increased income does not automatically translate into improved household welfare, as most earnings are absorbed by basic consumption needs and production continuity. In conditions of limited access to infrastructure, markets, and formal Islamic financial institutions, the borsom system emerges as an informal economic institution embedded in patron–client relations between artisans and collectors. From an Islamic economic perspective, borsom functions as a short-term economic buffer grounded in the value of mutual assistance (ta‘āwun), enabling production stability and household survival. However, prolonged reliance on this system reinforces structural dependence, weakens bargaining power, and constrains the achievement of sustainable welfare (falah). This study contributes by integrating rural sociological analysis with Islamic economic principles to explain how informal institutions simultaneously support and limit rural economic welfare. Strengthening inclusive Islamic financial institutions and diversifying rural livelihoods are essential for promoting more equitable and sustainable welfare outcomes.